Case report: Different clinical manifestations of the rare Loeffler endocarditis - Zhao, Yuanyuan; Jiang, Peiqing; Chen, Xiangyun; Yao, Guihua (Frontiers in Cardiovascular Medicine, 2022)
Background: Loeffler endocarditis is a rare and fatal disease, prone to misdiagnosis owing to its various clinical manifestations. Consequently, early identification and effective treatment are crucial for prognosis. Case Presentation: This report describes two cases of Loeffler endocarditis with different etiologies and clinical manifestations. Case 1 was caused by idiopathic eosinophilia and presented with a thrombus involving the tricuspid valve and right ventricular inflow tract (RVIT). The patient suffered from recurrent syncope following activity. After tricuspid valve replacement and thrombectomy, he took oral prednisone and warfarin for two years, and then he discontinued both drugs. However, the disease recurred 6 months later, manifesting as edema of both legs. Echocardiography showed that a thrombus had reappeared in the RVIT. Thus, oral prednisone and warfarin were administered again. Three months later, the thrombus had dissolved. Low-dose prednisone maintenance therapy was provided long-term. Case 2 involved a patient with recurrent fever, chest tightness, and asthma, whose condition had not been confirmed despite multiple local hospitalizations. In our hospital, echocardiography revealed biventricular apical thrombi. After comprehensive examinations, the final diagnosis was eosinophilic granulomatosis polyangiitis involving multiple organs, including the heart (Loeffler endocarditis), lungs, and kidneys. After administration of corticosteroid, anticoagulant, and immunosuppressive agents along with drugs to improve cardiac function, the patient's symptoms improved significantly. Conclusion: In Loeffler endocarditis due to idiopathic eosinophilia, long-term corticosteroid use may be required. Diverse and nonspecific symptoms cause Loeffler endocarditis to be easily misdiagnosed. Thus, when a patient shows persistent elevation of eosinophils with nonspecific myocardial damage, the possibility of this disease should always be considered. Further, even when an endomyocardial biopsy is not available or acceptable, corticosteroids should be administered promptly to return eosinophil counts to the normal range, halting disease progression and reducing the mortality of patients.